Analysis of attitudes and factors influencing the organ transplantation decision among the rural population - Juszczak, Katarzyna; Michalak, Agnieszka; Gawłowicz, Kamila; Balcerzak, Anita; Jachimowicz, Violetta (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2016)
Introduction : Transplantation of organs, tissues and cells is a particular type of treatment that not only results in prolonged life, but also improves the quality of life. Often it is the only and last chance for people with end-stage organ failure. The dilemmas posed by transplants apply to both donors and recipients. This implies many legal, ethical and psychological problems [1]. Although the law in Poland stipulates that you can get the organs of any person who during his life has not opposed this, ultimately, the approval of the family in this case is still taken into account. It is therefore important that the public be aware of what laws apply to avoid painful experiences. The aim of the study was to obtain information on attitudes and factors affecting the decision to transplant organs from people diagnosed with brain death. Material and methods : The study involved 113 people aged 18 to 69 years. The study used an original questionnaire. Results : Almost half of the respondents (47.5%) considered that the death of a man occurs when the lack of heart rate and breathing is confirmed. For 90.2% of subjects, transplantation of organs from a deceased person is a second chance for life, especially for people with end-stage organ failure. Factors influencing the decision on organ transplantation according to the respondents are: education, the opinion of the Catholic Church, the knowledge of the will of the deceased and concern about the correctness of the doc- tor’s decision declaring brain death. An important factor is also the emotions associated with the death of a loved one. Knowledge about transplants is most commonly drawn from TV and the press. Conclusions : It was found that the society in general accepts transplantation. There is a need to promote awareness about organ transplantation.